HUBUNGAN ANTARA PENGETAHUAN, SIKAP DAN MOTIVASI DENGAN PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI PADA PEKERJA BAGIAN PRODUKSI PT. KATINGAN INDAH UTAMA, KABUPATEN KOTAWARINGIN TIMUR, PROVINSI KALIMANTAN TENGAH - Gunawan, Indra; Mudayana, Ahmad A (Unnes Journal of Public Health, 2016)
Background: Occupational health and safety was a thought and effort to ensure the integrity and perfection of both body and spirit. PT Katingan Indah Utama was a company Domestic Investment (DCI), which was engaged in oil palm plantations and management. Problems on PT. Katingan Indah Utama was the implementation of occupational safety and health that had basically been performed well but not maximum, especially in the use of Personal Protective Equipment (PPE) for workers at the production line. This study aimed at identifying the relationship between knowledge, attitude and motivation with the behavior of using self- protective equipment at production workers in PT. Katingan Indah Utama, Kotawaringin Timur, Central Kalimantan province.Methods: This was an observational analytic study with cross sectional approach. The sample of this study was all production workers of PT. Katingan Indah Utama, in the amount of 70 workers. Analysis of data used univariate, bivariat with statistical test of Chi-Square and multivariate analysis with logistics regression.Results: The results of the study showed no correlation between knowledge (p = 0.004) and the behavior of the use of self-protective equipment, there was a relationship between attitudes (p = 0.031) and the behavior of the use of self-protective equipment and there was a relationship between motivation (p = 0.022) and the behavior of using self- protective equipment. Multivariate analysis showed that variable of knowledge was the dominant variable related to the behavior of of self-protective equipment at the production workers of PT . Katingan Indah Utama with p value ( 0.002). Conclusion: There was a correlation relationship between knowledge, attitude and motivation with the behavior of using self-protective equipment at the production workers of PT. Katingan Indah Utama, East Kotawaringin, Central Kalimantan Province and variable of knowledge was the dominant variable related to the behavior of of self-protective equipment at the production workers of PT . Katingan Indah Utama, East Kotawaringin, Central Kalimantan Province.